2011
DOI: 10.1097/ccm.0b013e31820a9416
|View full text |Cite
|
Sign up to set email alerts
|

The influence of genetic variation in surfactant protein B on severe lung injury in African American children*

Abstract: Genetic variations in the gene coding for surfactant protein B are associated with more severe lung injury as indicated by the association of specific single nucleotide polymorphism genotypes and haplotypes with the need for mechanical ventilation in African American children with community-acquired pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…However, similar to adult studies, SP-B polymorphisms were associated with worse lung injury in AfricanAmerican children with community-acquired pneumonia (83). In contrast to adults, exogenous surfactant therapy has improved oxygenation and reduced mortality in children with ARDS (84,85).…”
Section: Surfactant Systemmentioning
confidence: 92%
“…However, similar to adult studies, SP-B polymorphisms were associated with worse lung injury in AfricanAmerican children with community-acquired pneumonia (83). In contrast to adults, exogenous surfactant therapy has improved oxygenation and reduced mortality in children with ARDS (84,85).…”
Section: Surfactant Systemmentioning
confidence: 92%
“…SP-BC/T1580 is functionally one of the most important (26,27). This SP-BC/T1580 polymorphism is not only associated with pneumonia and pneumonia-induced ARDS (21,28,29), but also with neonatal respiratory distress syndrome (RDS) (30), and interstitial lung disease (ILD) (31). The detailed mechanisms for the increased susceptibility of SP-B C allele to these pulmonary diseases are unknown (6,27,32).…”
Section: Resultsmentioning
confidence: 99%
“…The Institutional Review Board from each institution approved the study. Some members of this cohort have been used in studies reported in previous publications (3537). As the frequency of genetic polymorphisms and the linkage disequilibrium (LD) patterns differ between ethnicities and races (38, 39), such groups should be analyzed separately (40).…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion and exclusion criteria as well as data collection for children with CAP have been described in detail in previous publications (3537). In brief, CAP was defined by 1) an acute illness (<14 days of symptoms); 2) the presence of a new chest radiographic infiltrate or consolidation confirmed by a radiologist; and 3) clinical features compatible with pneumonia, including one of the following: fever >37.8°C, hypothermia <36°C, peripheral white blood count >10,000/μL or <4500/μL, or >15% immature neutrophils; and two of the following: tachypnea (respiratory rate >2 standard deviations from the mean for age), dyspnea, or hypoxemia (pulse oximetry ≤94% on room air on initial evaluation without a known mixing heart lesion).…”
Section: Methodsmentioning
confidence: 99%